Intellectual Potential from the Other Side of Europe's Colonial and Nationalist Past: Cultural Science/Kulturwissenschaft around 1900 and its Relevance for Cultural Relations - Weigel, Sigrid; ifa (Institut für Auslandsbeziehungen) (Mannheim ; Stuttgart : SSOAR, GESIS - Leibniz-Institut für Sozialwissenschaften e.V. ; ifa (Institut für Auslandsbeziehungen), 2021)
Abstract: Currently cultural policy is increasingly determined by ideological controversies in which different theoretical programmes irreconcilably collide and Europe's history and culture - or more generally 'the West' - have become the most controversial subjects. After the past decades have witnessed a rapid sequence of different theories - critical theory, cultural studies, deconstructionism, new historicism, visual studies, post-colonialism, new materialism, to name just the most influential schools - the debate is presently becoming increasingly normative. It is morally charged by references to the European hegemonic and colonial past, and emotionally charged by identity politics and questions of belonging, based in ethnicity, gender, and origin. Against this background, this paper aims to remind us of the cultural-political and epistemological potential of a particular movement in intellectual history named Kulturwissenschaft (cultural science), which emerged from the reverse side of